Russian Baptists and spiritual revolution, 1905-1929 - Coleman, Heather J., 1968- (Indiana-Michigan series in Russian and East European studies., 2005)
Reconstructs the experiences of the Baptists in Russia in a dramatic period of social, economic, and political change.